2019
DOI: 10.3390/catal9030245
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dilute Acid and Alkali Pretreatments on the Catalytic Performance of Bamboo-Derived Carbonaceous Magnetic Solid Acid

Abstract: Lignocellulose is a widely used renewable energy source on the Earth that is rich in carbon skeletons. The catalytic hydrolysis of lignocellulose over magnetic solid acid is an efficient pathway for the conversion of biomass into fuels and chemicals. In this study, a bamboo-derived carbonaceous magnetic solid acid catalyst was synthesized by FeCl3 impregnation, followed by carbonization and –SO3H group functionalization. The prepared catalyst was further subjected as the solid acid catalyst for the catalytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The observation is in agreement with the reports by other research groups that acid treatment interferes with the overall charge of the slurry and needs a neutralization process [25,26]. Moreover, Zhu et al, 2019 reported that the pretreatment liquor from acid pretreated biomass possesses a good catalytic activity that can be recycled to obtain reducing sugars from additional cellulosic biomass [27].…”
Section: Consequence Of Bioprocessing On Nmr Analysissupporting
confidence: 90%
“…The observation is in agreement with the reports by other research groups that acid treatment interferes with the overall charge of the slurry and needs a neutralization process [25,26]. Moreover, Zhu et al, 2019 reported that the pretreatment liquor from acid pretreated biomass possesses a good catalytic activity that can be recycled to obtain reducing sugars from additional cellulosic biomass [27].…”
Section: Consequence Of Bioprocessing On Nmr Analysissupporting
confidence: 90%
“…However, they are not appropriate for a scale-up process due to high capital cost and pressure [61,62]. Diluted acid pretreatment helps in easy sugar conversion and it reduces the damage to equipment by corrosion; however, it has a longer reaction time [63]. Other pretreatments, such as the Soxhlet and Soxhlet-liquid (two-stage) pretreatment, are time-consuming, which could be a bottleneck.…”
Section: Summary Of Pretreatment Of Orange Peelmentioning
confidence: 99%
“…They aimed at improving the efficiency of the hydrolysis of the polysaccharides [11][12][13] to release second-generation sugars (xylose and glucose), furfural, 5-hydroxymethylfurfural (HMF), levulinic acid (LA) and formic acid (FA) [14][15][16][17][18][19][20][21]. A large number of pretreatments were reported in the literature employing mineral acids [22][23][24], inorganic salts [25,26], alkaline solutions [23,27], ionic liquids [28,29], and organosolv [30,31], in addition to physico-chemical techniques, such as steam explosion [32]. The choice of suitable pretreatment strongly depends on the biomass fraction that should be exploited and on the target products.…”
Section: Introductionmentioning
confidence: 99%